Business Model Canvas : Ample Power Company / Noor Amira Zaharlim - Zaharlim, Noor Amira (2020)
Ample Power Company was established on 2018. Our company produce food bowls that can handle smartphones. We create such product because nowadays people love to eat and using their phones at the same time. Some people always on their phones because of work. Therefore, we decided to invent a new product development called SMART Bowl. SMART Bowl is not just a food bowl that can handle smartphones, but it also has charging pod. We provide two types of charging pod which is wireless charging and also usb charging because there are some phones that do not support wireless charging. That is why we called the food bowl as ‘SMART Bowl’ because of the ability to hold and charge smartphones. Ample Power Company has a unique features on its product. The first thing is their unique colour of their product. SMART Bowl came out with a colour that does not exist in the market such as red, blue and purple colour. The colour we made it shiny finish. We wanted to make our product different and become a trend in youth society. On the other hand, our customer can request what type of charging module they want because certain phones do not support wireless charging. We provide usb for Android users and also iOS users. We provide 3 months warranty on every purchase. If there is any problem with the food bowl, they can send to us and we can change them a new bowl